2010
DOI: 10.3233/ch-2010-1260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E on reperfusion injuries during reconstructive vascular operations on lower limbs

Abstract: Introduction: The challenge against reperfusion injury and tissue oxidative stress, especially in vascular surgical interventions has an essential importance to reach the optimal clinical result. Numerous experimental attempts have proved the positive antioxidant effect of vitamin E in both chronic and acute phase models. In our study we monitored the effect of continuous preoperative treatment with vitamin E, on oxidative stress and tissue inflammation reactions developed after reconstructive operations.Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Gennari et al ( 33 ) and Dionigi et al ( 34 ) revealed that the lymphocytopenia that occurred after major surgery, stemmed from neuroendocrine stress and led to cortisol production, which ultimately caused lymphocytopenia in the peripheral blood. Additionally, decreased lymphocytes observed after myocardial infarction (MI), have been linked to injuries connected with ischemia-reperfusion (IR) ( 35 ). The current data demonstrated that in patients undergoing cardiac surgery with CPB, the total lymphocyte count conveys powerful prognostic information ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gennari et al ( 33 ) and Dionigi et al ( 34 ) revealed that the lymphocytopenia that occurred after major surgery, stemmed from neuroendocrine stress and led to cortisol production, which ultimately caused lymphocytopenia in the peripheral blood. Additionally, decreased lymphocytes observed after myocardial infarction (MI), have been linked to injuries connected with ischemia-reperfusion (IR) ( 35 ). The current data demonstrated that in patients undergoing cardiac surgery with CPB, the total lymphocyte count conveys powerful prognostic information ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many medical treatment options such as recombinant human BCL2 protein, ethyl pyruvate, laser therapy, hydrogen sulfide, PJ 34, poloxamer 188, ketamine, recombinant human VEGF165 protein, activated protein C, adenosine A, bortezomib, MRS2693, hypertonic saline solution, cariporide, grape seed proanthocyanin extract, Wisconsin solution, ultrasound, erythropoietin, resveratrol, vitamin E, 12 amino acid peptides have been experimentally studied and all of them were reported to have positive effects at some degree. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] However, studies on all these agents remained experimental and these agents failed to find a place in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, vitamin C prevents histamine release and increases the detoxification of histamine (Johnston, Martin, and Cai, 1992), thus acting as an anti-inflammatory agent as well as a potent antioxidant. Vitamin E on the other hand has been shown to be cardioprotective against tobacco smoke-induced peroxidative damage (Al-Malki and Moselhy, 2013; Gumustekin, Taysi, Alp, Aktas, Oztasan, Akcay, Suleyman, Akar, Dane, and Gul, 2010; Koul, Singh, and Sandhir, 2003) and can be a beneficial adjuvant in the treatment of seizures, diabetes and in the reduction of post-ischemic damages (Arato, Kurthy, Sinay, Kasza, Menyhei, Hardi, Masoud, Ripp, Szilagyi, Takacs, Miklos, Bator, Lantos, Kollar, Roth, and Jancso, 2010; dos Santos, Costa, Tome, Saldanha, de Souza, Feng, and de Freitas, 2011; Gupta, Sharma, Kaushik, and Shekhawat, 2011; Venditti, Napolitano, Di, Agnisola, and Di, 2011). Recently published in vitro studies by our group have clearly shown that both vitamin C and E can effectively protect the BBB against CSE-generated oxidative damage (Hossain, Mazzone, Tierney, and Cucullo, 2011b).…”
Section: Discussionmentioning
confidence: 99%